MAHASISWA KESEJAHTERAAN SOSIAL SEBAGAI AGEN PERUBAHAN TERHADAP ANAK-ANAK DI PANTI - Harefa, Selfian (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Fieldwork practicum that exists among students is not a new thing in the world of lectures has become an obligation and requirement of every university in the learning process. It also becomes a final task in completing studies. Social welfare study program expects students to be able to carry out practical field work well, not only to implement knowledge but to produce changes that are beneficial to the community or beneficiaries. One of the social welfare students made a change to the children of the Ora Et Labora Nusantara orphanage, Medan Petisah where the field work practicum was held. Change agents form a study group, this is based on the group work method. In carrying out social interventions, of course, there are several stages starting from the preparation stage, assessment stage, planning, action plan formulation stage, implementation, evaluation, termination. Social welfare students make a mini-project about Language Education (learning to speak Indonesian). This language education is carried out because many children there are still passive in using good and correct Indonesian because every day, they use the local language where they live, lack of parental attention, lack of interaction with others and lack of good knowledge. The author hopes that what social welfare students done can help improve human resources and of course help orphanage children who need help.